Exploiter les corpus vidéo à des fins de recherche : innovations méthodologiques et effets sur les pratiques en sciences de l’éducation - Serge Leblanc; Cyrille Gaudin (Éducation et Socialisation)
Video technology has undergone rapid high-tech advances over the last ten years, and it now offers a rich potential for researchers in education sciences. The aim of this article is to study the links between innovations in the use of video corpora in education sciences research that have emerged at a given moment in the French scientific landscape, and the changes in researchers’ practices that these innovations have (or have not) induced, provoked, or favored. Working from a synthetic report, first of all, three innovations deemed particularly significant for research have been selected. The most pertinent documentary and experiential resources regarding these innovations have then been researched and grouped together. Finally, they have been restituted in their specific scientific, historic, social, and technological contexts and then analyzed in order to understand the changes with which they have (or have not) gone hand-in-hand, taking into consideration questions of temporality.